The Effect of Investment Decisions, Funding Decisions, Operational Decisions on Value of the Firm through Financial Distress as Intervening and Good Corporate Governance (GCG) as Moderating - Rachmadani, Adelia Putri; Ratnawati, Tri; Brahmayanti, Ida Ayu Sri (PT Inovasi Pratama Internasional, 2024)
This research focuses on companies engaged in manufacturing because manufacturing companies are one of the important things for economic growth in Indonesia. Indonesian manufacturing companies are currently not diversified and only export relatively few types of products. This study aims to prove and analyze the relationship between investment decisions, funding decisions, operational decisions, financial distress, GCG on firm value. The sample in this study namelya manufacturing company engaged in the industrial sector listed on the Indonesia Stock Exchange (IDX) with a financial reporting period of 3 years, period 2019 to 2021. Tests were carried out using SmartPLS with an analysis of the outer model test and the inner model test. The research results show that operational decisions have a significant effect on financial distress, operational decisions have a significant effect on firm value andGood Corporate Governance (GCG)on firm value has a significant effect. The relationship of other variables shows no significant results on financial distress and firm value.